2010
DOI: 10.1093/hmg/ddq341
|View full text |Cite
|
Sign up to set email alerts
|

Molecular signature of primary retinal pigment epithelium and stem-cell-derived RPE cells

Abstract: Age-related macular degeneration (AMD) is characterized by the loss or dysfunction of retinal pigment epithelium (RPE) and is the most common cause of vision loss among the elderly. Stem-cell-based strategies, using human embryonic stem cells (hESCs) or human-induced pluripotent stem cells (hiPSCs), may provide an abundant donor source for generating RPE cells in cell replacement therapies. Despite a significant amount of research on deriving functional RPE cells from various stem cell sources, it is still unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
171
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(184 citation statements)
references
References 28 publications
12
171
0
1
Order By: Relevance
“…These data also revealed that iPSC-3-RPE maintained expression of cell cycle markers on day 30 at passage 3, which could suggest incomplete maturation/differentiation of these cells. These data are supported by previous findings that show iPSC-RPE maintains hypermethylation of cell adhesionrelated genes (hypomethylated in fRPE) 50 and gene expression profiles indicative of an immature RPE differentiation status 51 when compared to fRPE. The lagging maturity of the directed cells could explain the decreased RPE65 expression trend seen in Fig.…”
Section: Discussionsupporting
confidence: 89%
“…These data also revealed that iPSC-3-RPE maintained expression of cell cycle markers on day 30 at passage 3, which could suggest incomplete maturation/differentiation of these cells. These data are supported by previous findings that show iPSC-RPE maintains hypermethylation of cell adhesionrelated genes (hypomethylated in fRPE) 50 and gene expression profiles indicative of an immature RPE differentiation status 51 when compared to fRPE. The lagging maturity of the directed cells could explain the decreased RPE65 expression trend seen in Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Feng et al [24] reported that iPS-IMR90-1 and iPS-foreskin-2 did not form RPE colonies that could be propagated. Most recently, Liao et al [53] examined six iPS lines generated from endodermal and neuroectodermal lineages and found very low production of RPE colonies. Furthermore, other iPS lines driven to retinal and RPE phenotypes using factors were reported to be similar to hES [31].…”
Section: Discussionmentioning
confidence: 99%
“…To determine how the HTRA1/ARMS2 risk allele at 10q26 causes AMD, we make use of new technologies in stem cells and protein biology. RPE is generated from patients' own skin cells through induced pluripotent stem (iPS) cells, yielding matched RPE that expresses key molecular markers (Liao et al., 2010). This allows us to study patient‐specific genomes.…”
Section: Introductionmentioning
confidence: 99%